Resource reduction in pediatric chest pain: Standardized clinical assessment and management plan. (24th September 2017) - Saleeb, Susan F.; McLaughlin, Sarah R.; Graham, Dionne A.; Friedman, Kevin G.; Fulton, David R.
Abstract: Objective: Using a Standardized Clinical Assessment and Management Plan (SCAMP) for pediatric patients presenting to clinic with chest pain, we evaluated the cost impact associated with implementation of the care algorithm. Prior to introduction of the SCAMP, we analyzed charges for 406 patients with chest pain, seen in 2009, and predicted 21% reduction of overall charges had the SCAMP methodology been used. The SCAMP recommended an echocardiogram for history, examination, or ECG findings suggestive of a cardiac etiology for chest pain. Design: Resource utilization was reviewed for 1517 patients (7‐21 years) enrolled in the SCAMP from July 2010 to April 2014. Results: Compared to the 2009 historic cohort, patients evaluated by the SCAMP had higher rates of exertional chest pain (45% vs 37%) and positive family history (5% vs 1%). The SCAMP cohort had fewer abnormal physical examination findings (1% vs 6%) and abnormal electrocardiograms (3% vs 5%). Echocardiogram use increased in the SCAMP cohort compared to the 2009 historic cohort (45% vs 41%), whereas all other ancillary testing was reduced: exercise stress testing (4% SCAMP vs 28% historic), Holter (4% vs 7%), event monitors (3% vs 10%), and MRI (1% vs 2%). Total charges were reduced by 22% (822 625) by use of the Chest Pain SCAMP, despite a higher percentage of patients for whom echocardiogram was recommended compared to the historic cohort. Conclusions: The Chest Pain SCAMP effectively streamlines cardiac testing and reduces resource utilization. Further reductions can be made by algorithm refinement regarding echocardiograms for exertional symptoms.